(untitled) (Washington, D.C., 2006)
"This second edition of Disease Control Priorities in poor Developing Countries, published in conjuction with al companion book, by Alan Lopez and others, Global Burden of Disease and Risk Factors, serves as a roadmap for thishis challenge. It is a landmark reference for physicians,loping researchers, policymakers, and politicians who makeion book, decisions about improving the health of people in thend Risk developing world...The second edition of Disease Controla Priorities in Developing Countries will provide a new menu of activities from which its readers can choose to continue the most sensible path toward investing in health, removing inequities in health care, and promoting economic development and peace."--New England Journal of Medicine
Keywords: Developing countries,Public health; Social aspects,Prevention